1995
DOI: 10.1159/000244229
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Bilirubin Clearance from Rat Brain Regions

Abstract: The mechanism for the preferential distribution of bilirubin to basal ganglia (‘kernicterus’) is unknown. We hypothesized that differences in bilirubin clearance rates between brain regions might explain this phenomenon. Bilirubin [30mg/kg over 5 min, with 370-740 kBq (10-20 μCi) tritiated bilirubin] was infused into a peripheral vein in unanesthetized, young Sprague-Dawley rats (n = 36, weight 149 ± 15 g, mean ± SD). After blood sampling, groups of rats were killed at 15, 30, 45, 60, 75, 180, and 360 min with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…The half-life of bilirubin found in this study (18.5 ± 28.3 min in the control group) is very close to the half-life of 16.1 ± 7.7 and 18.5 ± 21.5 min, respectively, found in two previous studies [14,45]. In those studies pHJ-bilirubin was used, raising the possibility of underestimating the rate of clearance.…”
Section: Brain Bilirubin In Hemolytic Anemiasupporting
confidence: 87%
“…The half-life of bilirubin found in this study (18.5 ± 28.3 min in the control group) is very close to the half-life of 16.1 ± 7.7 and 18.5 ± 21.5 min, respectively, found in two previous studies [14,45]. In those studies pHJ-bilirubin was used, raising the possibility of underestimating the rate of clearance.…”
Section: Brain Bilirubin In Hemolytic Anemiasupporting
confidence: 87%
“…Thus, the experimental conditions used in our experiments were patterned on those previously shown to result in significant bilirubin concentrations in the brain. Under similar conditions the half-life of bilirubin in whole brain has been between 16.1 Ϯ 7.7 (13) and 18 Ϯ 21.5 min (mean Ϯ SD) (10). Similarly, the half-life in hippocampus has been 17.1 Ϯ 8.9 (13) to 19.0 Ϯ 21.5 min (10).…”
Section: Bilirubin Inhibits Ltp In Rat Brainmentioning
confidence: 87%
“…The observation time in our experiments was therefore equivalent to 6 -7 half-lives, suggesting that there may be residual effects of bilirubin neurotoxicity at a time when only minimal amounts of bilirubin remain in the brain. Previous studies found that bilirubin can be detected in the brain at 15 min after administration (10,13). Although the brain bilirubin concentrations have not been quantitatively measured in our study, we started our electrophysiological observation 1 min after bilirubin infusion and had actually noted significant effects on PS as well as on LTP.…”
Section: Bilirubin Inhibits Ltp In Rat Brainmentioning
confidence: 88%
See 1 more Smart Citation
“…Although information is available regarding bilirubin concentrations in whole brain and brain regions during induced hyperbilirubinemia in experimental animals (17)(18)(19)(20)(21)(22), no studies are on record which track bilirubin entry into cells and subcellular compartments in vivo. The purpose herein was to study the subcellular localization of bilirubin in rat brain after in vivo administration of radioactively labeled bilirubin.…”
mentioning
confidence: 99%